Tensile and Compressive Properties of Kaolin Rienforced Epoxy - Mohmmed, Jabbar Hussein (Al-Khwarizmi Engineering Journal, 2015)
Abstract The toughening of epoxy resins with the addition of organic or inorganic compounds is of great interest nowadays, considering their large scale of applications. In the present work, composites of epoxy are synthesized with kaolin particles having different particle sizes as reinforcement. Composites of epoxy with varying concentration (0 to 40 weight %) of kaolin was prepared by using hand lay method. The variation of mechanical properties such as modulus of elasticity, yield, tensile, and compressive strength with filler content was evaluated. The composite showed improved modulus of elasticity and compressive properties on addition of filler. In contrast, the tensile and yield strength of the composites decreases with rising kaolin content. It is also observed that mechanical properties increase with decrease in particle size in all cases. Keywords: mechanical properties, composite materials, epoxy risen, and kaolin.